Novel Lung Cell-Penetrating Peptide Targets Alveolar Epithelial Type II Cells, Basal Cells, and Ionocytes - Jin Wen; Gajalakshmi Singuru; Jeffrey Stiltner; Sanjay Mishra; Kyle S. Feldman; Kayla McCandless; Raymond Yurko; Kazi Islam; Ray Frizzell; Hisato Yagi; Jonathan M. Brown; Maliha Zahid (Pharmaceutics)
Background: Cell-penetrating peptides cross cell membrane barriers while carrying cargoes in a functional form. Our work identified two novel lung-targeting peptides, S7A and R11A. Here, we present studies on biodistribution, the cell types targeted, and an in vitro proof of application. Methods: Studies were performed in human bronchial epithelial cells (HBECs) with and without various endocytic inhibitors, and coincubation with fluorescently labeled transferrin or endocytic markers. Cyclic R11A (cR11A) was conjugated to siRNA duplexes and anti-viral activity against SARS-CoV-2 was tested. Biodistribution studies were performed by injecting wild-type mice with fluorescently labeled peptides, and various circulation times were allowed for, as well as cross-staining of lung sections or isolated single cells with various cellular markers, followed by fluorescence-activated cell sorting or confocal microscopy. Results: cR11A showed peak uptake in 15 min, with the highest uptake in airway epithelial type II (ATII) cells, followed by p63+ basal cells and ionocytes. Cyclization increased transduction efficiencies ~100-fold. Endocytosis studies showed a decrease in peptide uptake by pre-treatment with Pitstop2 but not Amiloride or Nystatin. Endocytic marker Lamp1 showed colocalization at the earliest time point, with the escape of the peptide from endocytic vesicles later. cR11A conjugated to ant-spike and anti-envelop proteins showed anti-viral effects with an EC90 of 0.6 μM and 1.0 µM, respectively. Conclusions: We have identified a novel peptide, cR11A, that targets ATII, basal cells, and ionocytes, the cyclization of which increased transduction efficiency in vitro and in vivo. The uptake mechanism appears to be via clathrin-mediated endocytosis with escape from endocytic vesicles. cR11A can act as a vector to deliver anti-viral siRNA to epithelial cells.